Potential for the valorisation of brewer's spent grains A case study for the sequential extraction of saccharides and lignin - de Crane d'Heysselaer, Simon (Waste management & research : the journal of the International Solid Wastes and Public Cleansing Association, ISWA, 2022)
This study highlights the possibility of using brewers' grains (BSGs) for the successive extraction of the main lignocellulosic biopolymers, namely, cellulose, hemicelluloses and lignin. An exhaustive chemical characterisation revealed a variability of composition in distinct batches of BSGs, depending on their origin and the brewing process used. In particular, the protein content can vary from 13wt% to 23wt%, which is accompanied by a change in the hemicelluloses content from 9% to 23% (in the samples of our study). By applying a two-step aqueous treatment, involving an acid (1.25% v/v aq. H2SO4) and a base (3% w/v aq. NaOH) at a temperature of 120°C and fixed reaction time of a few tens of minutes (15-90 minutes), more than 80% of hemicelluloses could be recovered. Cellulose could be isolated at more than 68%, while a high purity lignin could be recovered from a lignin-rich fraction (70wt%). Our work also suggests that the variability of the chemical composition of these BSGs is a hindrance to achieving process standardisation and large-scale exploitation. The pooling of various materials is therefore not a recommended option, and the preliminary chemical analysis of the composition is therefore a prerequisite for an efficient extraction process